Complete mucosal healing defined by endoscopic Mayo subscore still demonstrates abnormalities by novel high definition colonoscopy and refined histological gradings - Iacucci, Marietta; Fort Gasia, Miriam; Hassan, Cesare; Panaccione, Remo; Kaplan, Gilaad G.; Ghosh, Subrata; Gui, Xianyong (Endoscopy, 2015)
Background and study aims: A novel high definition colonoscopy imaging technique (i-Scan) can characterize, in detail, colonic mucosa in patients with ulcerative colitis, and may provide additional information about mucosal healing. The aim of this study was to create a more refined histological and endoscopic criteria based on this novel technique in order to redefine inflammatory activity and mucosal healing. Patients and methods: A total of 78 patients with ulcerative colitis were assessed by high definition colonoscopy as well as by white light endoscopy (WLE). Mayo endoscopic subscores were assigned to patients according to WLE findings. Mucosal and vascular patterns on high definition colonoscopy were each graded from 1 – 4. A histological scoring system (ECAP system) was designed to reflect all histological changes in ulcerative colitis. Results: The overall high definition imaging scores (mucosal and vascular patterns) were significantly correlated with Mayo endoscopic subscores (rs = 0.86, 95 % confidence interval [CI] 0.79 – 0.91; P < 0.0001). Of those with Mayo endoscopic subscore of 0, 30.4 % had an abnormal mucosal pattern and 73.9 % of them had an abnormal vascular pattern on high definition colonoscopy; a score of 6 or less had a sensitivity of 95.8 % (95 %CI 85.7 % – 99.3 %) and specificity of 75.9 % (95 %CI 56.5 % – 90.0 %) to detect mucosal healing as defined by Mayo endoscopy subscore of 0 or 1. Furthermore, mucosal and vascular pattern scores were also significantly correlated with most parameters of the proposed ECAP score.Conclusion: The subtle histological abnormalities underlying the apparently healed mucosa in ulcerative colitis could be detected using high definition colonoscopy and the refined ECAP histology scoring system. These techniques detect residual abnormalities in the majority of patients with seemingly complete mucosal healing by conventional Mayo criteria.